Penyuluhan Manfaat Buah Bit Dalam Pencegahan Anemia Dan Meningkatkan Kadar Hemoglobin Pada Ibu Menyusui Dimajalengka - Oktafirani Al Sas; Fiki Setiawan; Usdiyanto Usdiyanto; Supriyatin Supriyatin; Ikhwani Ikhwani; Nita Nurhayati (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
Anemia is one of the conditions in which the body lacks enough red blood cells or hemoglobin to meet its physiological needs depending on the person's age, gender, age, pregnancy stage and breastfeeding stage because at the breastfeeding stage, the mother is susceptible to experiencing anemia due to iron depletion during breastfeeding and the occurrence of postpartum blood loss. Beetroot (Beta Vulgaris) is a fruit that contains quite high iron and has many nutrients. Beetroot can be used as an alternative to anemia treatment and can also be used as a prevention of anemia. The purpose of this community service activity is to give beets to breastfeeding mothers, namely to increase the knowledge of breastfeeding mothers about the benefits of beets in preventing and treating anemia. The method used in this activity is counseling by means of socialization first then followed by observation using questionnaires and blood sampling for hemoglobin examination. This activity took place at the Posyandu Sukasari Kaler Village, Majalengka Regency on April 14 – 21, 2023. Based on the results of community service activities, we can know that consuming beets for 7 days can prevent anemia and increase hemoglobin levels in breastfeeding mothers.